Self-Strangulation by Vehicle-Assisted Ligature Without Decapitation: A Case Report and A Review of the Literature - W, Ben Amar; H, Siala; M, Zribi; N, Karray; Z, Hammami; Z, Khemekhem; S, Maatoug (Archives of Clinical and Medical Case Reports, 2021)
Background: Self-strangulation with a vehicle-assisted ligature is reported to be very uncommon suicidal method. Related cases are rarely published, and many of them report massive injuries to neck organs, and even complete decapitation. Case presentation: We report an unusual case of self-strangulation where a body was found dead inside a car with a rope around his neck and tied to an electric pole behind the car. The rope didn’t break while the car moved away, and no decapitation was associated. The manner of death was determined as suicide based on a complete criminal investigation supported by a detailed crime scene investigation and autopsy. Conclusion: This case is reported for its originality due to the unusual method of suicide employed by the victim, and because it was not related to decapitation.